Case Report: Unmasking Hypercalcemia in Patients With Neuroendocrine Neoplasms. Experience From Six Italian Referral Centers - Giannetta, Elisa; Sesti, Franz; Modica, Roberta; Grossrubatscher, Erika Maria; Guarnotta, Valentina; Ragni, Alberto; Zanata, Isabella; Colao, Annamaria; Faggiano, Antongiulio (Frontiers in Endocrinology, 2021)
Background Hypercalcemia is a common paraneoplastic syndrome which can occur in up to 10% of patients with advanced neoplasms. Paraneoplastic parathyroid hormone-related protein (PTHrP) represents the most frequent cause of this syndrome. In neuroendocrine neoplasms (NENs) paraneoplastic hypercalcemia is rare. Case Series The present series includes all patients with NENs and paraneoplastic hypercalcemia from four Italian centres: (i) A 40-year-old man was hospitalized for repeated episodes of falls, hyposthenia and drowsiness. A severe hypercalcemia was found. Metastatic pancreatic G2 NEN and PTHrP-related hypercalcemia were diagnosed. The patient started therapy with somatostatin analogs (SSA) and Denosumab. After disease progression peptide receptor radionuclide therapy (PRRT) was started with an objective response associated with PTHrP reduction and normocalcemia. (ii) A 45-year-old man was referred for pancreatic G2 NEN. SSA and subsequently everolimus were administered for metastases occurrence. Hypercalcemia due to PTHrP secretion occurred. PRRT and Denosumab were started for disease progression with the onset of bone metastases. Despite disease stability after 4 cycles of PRRT the patient’s performance status worsened until death. (iii) A 49-year-old woman was hospitalized for psychic slowdown, confusional state, sensory dullness. A severe hypercalcemia, associated with a pancreatic G1 NEN was diagnosed and treated with haemodialysis, bisphosphonates injections and continuous infusion of calcitonin. 1,25-dihydroxyvitamin D was high, PTHrP was undetectable. After surgery serum calcium levels and 1,25-dihydroxyvitamin D were normalized. (iv) A 69-year-old man was hospitalized after the onset of shortness of breath and dyspnea, asthenia and weight loss. Computed Tomography (CT) and 68Ga DOTATOC PET-CT revealed a left pulmonary nodule. Hypercalcemia and markedly elevated PTHrP levels were detected. The histological examination revealed an atypical carcinoid. After surgery, calcium levels were normalized, PTHrP was significantly reduced with an improvement of general conditions. Conclusion In our NENs’series the paraneoplastic PTHrP-related hypercalcemia occurred mainly in pancreatic NEN, except for one bronchial carcinoid representing the third case in literature. Our case associated to 1,25-dihydroxyvitamin D secretion represents the fourth case in literature. PTHrP secretion should be considered in NENs’patients with hypercalcemia. Acute treatment should be focused on lowering calcium levels, and long-term control can be achieved by tumor cytoreduction inhibiting PTHrP release